Axial compressive behavior of square steel tubular columns filled with steel stirrups reinforced recycled lump concrete. (February 2022) - Zang, Jian-Bo; Wu, Bo
Abstract: Without increasing the total steel usage, a square concrete filled steel tubular (CFST) column with internal steel stirrups and relatively thinner steel tube exhibits a superior fire resistance over a traditional CFST column without stirrups, but there are few studies on the former's axial compressive behavior at ambient temperature. Fourteen square concrete filled steel tubular columns with internal steel stirrups and six control columns without stirrups were tested under pure axial loading. The concrete filling was incorporated with lumps of recycled concrete, which can be a feasible solution for recycling and reusing waste concrete. The test results showed that: (1) with the same total steel usage, the internal stirrups slightly decrease a column's ultimate capacity, but they significantly improve the ductility and post-peak deformability; (2) including lumps of recycled concrete in the fill has little effect on the axial compressive behavior up to a replacement ratio of 30%. The experimental data are compared with the predictions of existing design standards and empirical methods, and one of the methods is extended to predict the ultimate capacity of columns with internal stirrups containing lumps of recycled concrete.